Analisis Putusan Nomor 70/Pid.Sus/2024/Pn Jmr: Permufakatan Jahat Dalam Tindak Pidana Narkotika - Pamungkas, Teguh Karya; Azhelia, Rinda Izza; Ilyasi, Ach. (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
His study analyzes Verdict Number 70/Pid.Sus/2024/PN Jmr, which examines the application of Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, related to criminal conspiracy in narcotics crimes. Criminal conspiracy refers to a form of agreement between two or more people to commit a crime, even though the crime has not been fully executed. This study aims to evaluate how the court applies this article to prove the defendants' involvement in a narcotics network. The research findings show that the panel of judges used electronic communication evidence, physical evidence of narcotics, and witness testimonies to prove the conspiracy between the defendants. The court ruled that even though the narcotics distribution had not occurred, the malicious intent realized through joint planning was sufficient to impose sanctions. The severe punishment given to the defendants aligns with the government's policy in combating narcotics crimes. This analysis also found challenges in proving criminal conspiracy, particularly regarding the use of indirect evidence such as non- physical communication. Additionally, there is a discussion regarding the proportionality of the punishment, especially for those with minor roles in the narcotics network. In conclusion, the application of the criminal conspiracy article is effective in enforcing narcotics law, but an evaluation of the standard of proof and proportionality of punishment is needed to ensure a more balanced justice system.